2014
DOI: 10.1542/peds.2013-2059
|View full text |Cite
|
Sign up to set email alerts
|

In-School Neurofeedback Training for ADHD: Sustained Improvements From a Randomized Control Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: An estimated 9.5% of children are diagnosed with attention-deficit/hyperactivity disorder (ADHD), which affects academic and social outcomes. We previously found significant improvements in ADHD symptoms immediately after neurofeedback training at school. WHAT THIS STUDY ADDS:This randomized controlled trial included a large sample of elementary school students with ADHD who received in-school computer attention training with neurofeedback or cognitive training. Students who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 40 publications
1
97
0
2
Order By: Relevance
“…Although blinding of participants, parents, and teachers was not attempted in this study, blinded behavioral classroom observations indicated a significant reduction (ES 5 0.43) of verbal-motor ADHD (off-task) behaviors corresponding to hyperactivity/impulsivity after the intervention, 47 as well as at follow-up when using a nonlinear model of change. 48 The advantage of neurofeedback was also maintained for blinded classroom observation when compared with an active computer training, including attention and working memory games of similar duration and intensity. However, when teacher ratings were used as the best blinded outcome for, 25,45 and when the classroom observations of inattention were included for, 49 following the protocol of, 11 these moderate effects were reduced substantially and no longer significant.…”
Section: Neurofeedback For Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although blinding of participants, parents, and teachers was not attempted in this study, blinded behavioral classroom observations indicated a significant reduction (ES 5 0.43) of verbal-motor ADHD (off-task) behaviors corresponding to hyperactivity/impulsivity after the intervention, 47 as well as at follow-up when using a nonlinear model of change. 48 The advantage of neurofeedback was also maintained for blinded classroom observation when compared with an active computer training, including attention and working memory games of similar duration and intensity. However, when teacher ratings were used as the best blinded outcome for, 25,45 and when the classroom observations of inattention were included for, 49 following the protocol of, 11 these moderate effects were reduced substantially and no longer significant.…”
Section: Neurofeedback For Adhdmentioning
confidence: 99%
“…However, interpretation of these findings is complicated by the fact that most ratings of long-term effects (except for the behavioral observation measure in Ref. 48 ) were not blinded and thus subject to bias.…”
Section: Stability Over Timementioning
confidence: 99%
“…Meta‐analyses of randomized controlled trials (RCT) of EEG‐NF show medium effect sizes for symptom improvements [Arns et al, 2009], reduced to trends when only “probably” blinded raters are included [Holtmann et al, 2014; Sonuga‐Barke et al, 2013]. Crucially, unlike psychostimulant treatment, NF effects seem stable and longer‐lasting (up to 2 years), with no side effects [Arns and Kenemans, 2014; Gani et al, 2008; Gevensleben et al, 2010; Leins et al, 2007; Mayer et al, 2016; Steiner et al, 2014; Strehl et al, 2006]. …”
Section: Introductionmentioning
confidence: 99%
“…More importantly, no other ADHD treatment has demonstrated credible evidence of sustained benefit following treatment termination, whereas this is the consistent finding of NFB studies that included follow-up assessments at 6 months (Gevensleben et al, 2010;Leins et al, 2007;Meisel, Servera, Garcia-Banda, Cardo, & Moreno, 2013;Steiner, Frenette, Rene, Brennan, & Perrin, 2014;Strehl et al, 2006) and 2 years (Gani, Birbaumer, & Strehl, 2008;Monastra, 2005).…”
Section: Adhdmentioning
confidence: 81%